Why Fight Poverty?. - Unwin, Julia (Perspectives (London Publishing Partnership), 2013)
Poverty, and calls to end it, date back centuries. Even in prosperous modern times, despite the huge transformation of society, poverty has persisted. This book looks back at the struggle to end poverty and asks if it is worth it.